Capital Structure and Financial Performance on Company Value with Company Size as an Intervening Variable - Nadila, Nadila; Lusiana, Lusiana; Sari, Desi Permata (GOVERNORS, 2024)
This study aims to determine the effect of capital structure and financial performance on firm value with firm size as an intervening variable in non-primary sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The sample selection technique used purposive sampling and obtained 27 non-primary sector companies. The data analysis technique used multiple linear regression analysis and path analysis using SPSS 26. Based on the results of the hypothesis, it shows that capital structure does not have a significant effect on firm size, financial performance does not have a significant effect on firm size, capital structure has a significant effect on firm value, financial performance has a significant effect on firm value, firm size has a significant effect on firm value, firm size is able to mediate the effect between capital structure on firm value, firm size is able to mediate the effect between financial performance on firm value in non-primary sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. It is hoped that this study can help non-primary sector companies listed on the Indonesia Stock Exchange (IDX) to increase their firm value by considering factors that have a significant effect on the firm value such as capital structure, financial performance, and firm size.